Mekanisme Penyelesaian Sengketa Sertifikat Hak Atas Tanah Ganda Oleh Kantor ATR/BPN Kabupaten Manggarai Barat - Antari, Putu Eva Ditayani; Yudha Negara, I Putu Wahyu; Putri Suteja, Ida Ayu Devina Aishwarya; Salvia, Merva Putri (Universitas Sebelas Maret, 2023)
Land is one of the organizers of life for human, and its value is increasing with the passage of the time. Land use value increases have both positive and negative consequences. The emergence of land conflicts is one of the negative consequences. Disputes over dual land rights certificates, or disputes over two (2) or more certificates that specify the same parcel of land, either totally or partially overlapping, are common in West Manggarai Regency. The Ministry of Agrarian and Spatial Planning/National Land Agency (ATR/BPN) has the authority to resolve defense disputes in Indonesia through non-litigation channels. Therefore, the problems examined in this study are what are the factors that cause disputes in the land sector and how is the mechanism for resolving disputes over dual land rights certificates in West Manggarai by ATR/BPN West Manggarai Regency. This research uses empirical legal research methods, types of primary legal materials and secondary legal materials with qualitative descriptive data analysis techniques. Based on PERMEN Agaria Number 21 of 2020 concerning the handling and settlement of land cases, the resolution of disputes over dual land rights certificates that can be carried out by the ATR/BPN of West Manggarai Regency is to seek the resolution of dual certificate disputes through non-litigation channels with mediation between the disputing parties. The mediation carried out by ATR/BPN West Manggarai is expected to be able to effectively assist the people of West Manggarai in resolving disputes over dual land rights certificates.